Design principles for plasmonic thin film GaAs solar cells with high absorption enhancement - Hong, Lei (2013)
In this paper, a systematic design and analysis of gallium arsenide thin film solar cells incorporated with a periodic silver nanoparticles (NPs) structure to enhance light absorption is presented using the finite element method. The influence of the silver nanoparticles diameter and structure periodicity on light absorption has been examined. It is found that the absorption is significantly enhanced due to the surface plasmon induced by the silver nanoparticles. The optimal structural parameters are achieved when the diameter of the nanoparticles is 200 nm and the periodicity is 444 nm. This gives rise to a maximum ultimate photocurrent of 26.32 mA/cm2 under AM1.5G solar irradiation. In addition, the underlying physics that accounts for the enhancement is discussed.